Medium effects on the spectroscopy and intramolecular energy redistribution of C₆₀ cryogenic matrices - Chergui, M. (Физика низких температур, 2000)
We review some of our works on the absorption, excitation and emission spectra of C₆₀ embedded in rare gas matrices while stressing the role of the environement. The gas phase resonant two-photon ionization spectrum of C₆₀ is reanalysed in the light of our previous work and the energy of the lowest three excited singlet states is determined with precision. In matrices, the visible absorption bands shift red by ~30 cm⁻¹ in Ne matrices to ~330 cm⁻¹ in Xe matrices. The observed reversal of state ordering of the lowest two singlets states (T₁g and T₂g ) between Ne and Ar matrices (in emission) and in Ne matrices, between absorption and emission spectra, is attributed to different Stokes shifts of the T₁g and T₂g states and to the small energy splitting (~50 cm⁻¹) between them. Finally, a detailed picture of the intramolecular energy redistribution processes is obtained thanks to a combination of picosecond fluorescence experiments and femtosecond pump-probe transient absorption experiments. The intramolecular relaxation processes among the pure electronic levels of the lowest three singlets states are found to be strongly medium dependent. Even, on the very short time scale of the internal conversion in the singlet vibronic manifold are medium effects manifest.